2017
DOI: 10.3390/min7060093
|View full text |Cite
|
Sign up to set email alerts
|

PbSO4 Leaching in Citric Acid/Sodium Citrate Solution and Subsequent Yielding Lead Citrate via Controlled Crystallization

Abstract: Lead citrate is a key precursor for the green recycling of spent lead acid battery paste in a citric acid/sodium citrate (CA/SC) solution. In this study, the main paste component, PbSO 4 , was leached and crystallized to yield lead citrate. Results showed that the leaching of PbSO 4 in citric acid/sodium citrate solution was remarkably enhanced by an increase in temperature from 35 • C to 95 • C and an increase in sodium citrate (SC) concentration from 50 to 650 g/L. In comparison, increasing the citric acid/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…Cuando aumenta la concentración de agente lixiviante la extracción disminuye a 80%, el cual industrialmente sigue siendo un valor atrayente. Los anteriores resultados indican que la actividad iónica es más alta a bajas concentraciones comparadas con las características de una solución con altas concentraciones, sin embargo, si domina el consumo de citrato de sodio en la reacción hidrolítica, la reacción compleja puede debilitarse o retardarse, lo que conduciría a un efecto inhibidor sobre el comportamiento del agente lixiviante [8,6]. En la Figura 8 se observa una disminución de extracción metálica y una menor influencia de la concentración de agente lixiviante en el proceso hidrometalúrgico; la extracción más alta (90%) se obtuvo para una relación sólido líquido 10:1 a 0.25 y 0.5 M de citrato; mientras que para una concentración de citrato 1 M se obtuvo 85%.…”
Section: Análisis De Resultadosunclassified
See 1 more Smart Citation
“…Cuando aumenta la concentración de agente lixiviante la extracción disminuye a 80%, el cual industrialmente sigue siendo un valor atrayente. Los anteriores resultados indican que la actividad iónica es más alta a bajas concentraciones comparadas con las características de una solución con altas concentraciones, sin embargo, si domina el consumo de citrato de sodio en la reacción hidrolítica, la reacción compleja puede debilitarse o retardarse, lo que conduciría a un efecto inhibidor sobre el comportamiento del agente lixiviante [8,6]. En la Figura 8 se observa una disminución de extracción metálica y una menor influencia de la concentración de agente lixiviante en el proceso hidrometalúrgico; la extracción más alta (90%) se obtuvo para una relación sólido líquido 10:1 a 0.25 y 0.5 M de citrato; mientras que para una concentración de citrato 1 M se obtuvo 85%.…”
Section: Análisis De Resultadosunclassified
“…En este artículo se desarrolló un análisis termodinámico del agente lixiviante citrato de sodio (Na 3 C 6 H 5 O 7 •2H 2 O) [5,6]; para la extracción de plomo obtenido de baterías de automóvil recicladas. El trabajo se llevó a cabo mediante el uso de técnicas mecánicas para el procesamiento de materiales, en conjunto de procesos químicos implementados en la hidrometalurgia.…”
Section: Introductionunclassified
“…Although the reaction temperature dropped significantly, still sulfur dioxide escaped due to the low desulfurization efficiency . Comparatively, sufficient conversion of sulfur can be achieved using hydrometallurgical technologies with various aqueous systems, including chlorine salts, , alkaline solutions (sodium carbonate, ammonium carbonate, sodium hydroxide, and so on), and organic acids. , Ye et al extracted lead from bioleaching residue tailings using sodium chloride successfully, based on the solubility of complexation chlorides. Buzatu et al studied the mathematical modeling of the sodium hydroxide leaching process, improving the leaching efficiency of lead sulfate.…”
Section: Introductionmentioning
confidence: 99%
“…18 Comparatively, sufficient conversion of sulfur can be achieved using hydrometallurgical technologies with various aqueous systems, including chlorine salts, 19,20 alkaline solutions (sodium carbonate, ammonium carbonate, sodium hydroxide, and so on), 21−23 and organic acids. 24,25 Recently, an alternative approach based on mechanochemistry for materials synthesis, 26−28 waste treatment, 29 and metal alloying, has received considerable attention due to its ecofriendliness and moderate operating conditions. Mehrabani et al demonstrated the preparation of metallic tungsten from scheelite via co-grinding with magnesium, revealing the positive effect of mechanochemistry on the chemical reduction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many studies about the treatment of Pb-containing wastes using pyrometallurgical and hydrometallurgical processes were reported in recent years [12,13]. The immobilization of lead slags to prepare construction materials and inorganic polymers were also investigated [14,15].…”
Section: Introductionmentioning
confidence: 99%